Addressing uncertainties in permafrost-climate interactions - Kwon, Min Jung; Walvoord, Michelle; Laurion, Isabelle; Schaepman-Strub, Gabriela; Domine, Florent; Koltz, Amanda; Voigt, Carolina (One earth (Cambridge, Mass.), 2025)
Peatlands and permafrost have accumulated and stored organic matter for millennia. Now, anthropogenic climate change is rapidly disrupting the biogeochemical processes of these environments, with potentially significant and globally impactful implications. However, the magnitude, drivers, and interactions of these changes are variable and remain highly uncertain. In this Voices, we asked: what are the key processes of permafrost and peatland change, and how can uncertainty be reduced?